(3GdQeGM aj HjGf Jedc GdMhGfjJ GdJi ddMHS HGdHjY hGdTQGAs - (3GdTQGjSjs ((3eQGcT s)
(3ChdgG (B:s
(3HYO adeG cGf GdeGd eeG GLJeY Ydi MaXg hYOe VjGYg s
(3BNQgG (B:s
(3hcGf GdaQGZ ef gPG GdJbjjO YGe (B1325 s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ , RNGQa s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdeGdcjs